2014
DOI: 10.4081/jlimnol.2014.910
|View full text |Cite
|
Sign up to set email alerts
|

Profundal benthic invertebrates in an oligotrophic tropical lake: different strategies for coping with anoxia

Abstract: The mg C m -2 ). C. patzcuaro is dominant and is present throughout the year, whereas Ch. austini is recorded only when the bottom water of the lake is oxygenated. A comparison with the analogous but temperate Lake Mergozzo in Italy illustrates the role that anoxia plays in tropical lakes by diminishing not only taxonomic richness (13 vs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…The original data presented in this study provide evidence of the plasticity observed for an endemic species which up to date has been found only in Lake Alchichica [ 36 ]. The hydrological cycles and the accompanying oscillations in the abiotic and biotic variables of Lake Alchichica have been widely documented for the last 20 years [ 30 , 61 ], so even though we analysed data from only one year, we judge our results reflect the response of the copepod population facing an average year. However, considering the subtle but apparently steady increase in water temperature observed the last years, it would be desirable to extend the survey to a longer period, as well as to include other species from neighbour waterbodies (in this lake, L .…”
Section: Discussionmentioning
confidence: 99%
“…The original data presented in this study provide evidence of the plasticity observed for an endemic species which up to date has been found only in Lake Alchichica [ 36 ]. The hydrological cycles and the accompanying oscillations in the abiotic and biotic variables of Lake Alchichica have been widely documented for the last 20 years [ 30 , 61 ], so even though we analysed data from only one year, we judge our results reflect the response of the copepod population facing an average year. However, considering the subtle but apparently steady increase in water temperature observed the last years, it would be desirable to extend the survey to a longer period, as well as to include other species from neighbour waterbodies (in this lake, L .…”
Section: Discussionmentioning
confidence: 99%
“…The deep benthic area of Lake Alchichica is stable (Tab. 1) with exception of the DO that is present only for four months (February-May), while the rest of the year the bottom water remains anoxic and H 2 S reaches up to 3.08 mg L -1 (Hernández et al, 2014). The substrate presented fine sediments with very high contents of organic matter, and carbonate.…”
Section: Resultsmentioning
confidence: 99%
“…However, as mentioned above, other species -but not Cletocamptus gomezi -are found along the slope at greater depths. Finally, at and below 50 m, only two species are found: an ostracod and a chironomid (Hernández et al, 2014). Both species are regulated by the long period (8 months) of anoxia and the presence of H 2 S at these depths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of benthic invertebrates in Lake Alchichica revealed the presence of ostracods in the littoral, sublittoral (Hernández et al, 2010) and profundal zones (Hernández et al, 2014). Among them, the recently described Limnocytherina axalapasco Cohuo-Durán, Pérez & Karanovic, 2014 was found in the shallow littoral area of Lake Alchichica (Cohuo-Durán et al, 2014).…”
mentioning
confidence: 97%